Genetic diversity and antimicrobial resistance profile of Enterococcus faecalis isolated from broilers with vertebral osteomyelitis in Southeast Brazil. Issue 1 (2nd January 2018) - Braga, Juliana Fortes Vilarinho; Leal, Carlos Augusto Gomes; Silva, Camila Costa; Fernandes, André Almeida; Martins, Nelson Rodrigo da Silva; Ecco, Roselene
ABSTRACT: Vertebral osteomyelitis (VO) is a worldwide emerging disease that affects broilers. Recently, the isolation of Enterococcus faecalis in cases of the disease has been described. This study aimed at determining the genetic diversity and antimicrobial resistance profile of 12 E. faecalis strains isolated from broilers with VO. Strains were isolated from nine flocks from six farms in a high-density poultry production area in Southeast Brazil and were evaluated using multilocus sequence typing and phylogenetic analysis. Antimicrobial susceptibility tests and PCR were performed to detect antimicrobial resistance genes. E. faecalis isolates belonged to different sequence types (ST), six of which (ST49, ST100, ST116, ST202, ST249, and ST300) have been previously described. Strains ST708 and ST709 were newly identified in this study. Strain ST49 was most frequently isolated (50% of the flocks) from the analysed VO cases. No phylogenetic or phylogeographic relationship was found among the strains. The VO isolated E. faecalis strains showed highest resistance to aminoglycosides, mainly gentamicin (40%), but were highly susceptible to vancomycin (10%). Aminoglycoside resistance genes were detected in seven E. faecalis strains, and AAC6′-APH2″ genes were most frequently detected. The results showed that E. faecalis strains isolated from recently reported VO cases were highly diverse genetically. The diversity of genotypes in circulation in the analysed flocks, without apparent relationship among them, raises questions on aetiopathogenesis of the disease in broilers and evolutionary aspects of E. faecalis .